Exploring the influence of halogen-substituted Cp*RuX catalysts on RuAAC [3 + 2] cycloaddition: A quantum mechanical investigation” - Khairbek, Ali A.; Al-Zaben, Maha I.; Puchta, Ralph; Thomas, Renjith (Computational and Theoretical Chemistry, 2025)
This study investigated the mechanism of azide-alkyne cycloaddition reactions catalyzed by complexes of ruthenium, specifically Cp*RuX complexes, with various halides (F, Cl, Br, and I). Using the MN12-L/Def2-SVP basis set for all the elements and the Def2-TZVP for Ru (including a pseudopotential for Ru and I) calculations, this research employs an advanced basis set and pseudopotential methods tailored for the elements involved, with a particular focus on the formation of a specific regioisomer. A comparison of the catalytic pathways revealed that the efficiency of the 1,5 pathway surpasses that of the 1,4 pathway in all the examined complexes, particularly when assessed in a common organic solvent. This study highlights the significant role of halogen identity in these complexes, establishing a catalytic activity trend influenced by the halogen used. Detailed analyses using several computational techniques were performed to examine the molecular structures, electron densities, and interactions, demonstrating the potential to enhance catalytic performance by carefully selecting substituted complexes. This research provides valuable insights for designing effective catalysts for click chemistry applications, emphasizing the impact of halogen substitution on catalytic efficiency.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Cp*RuX; Density functional theory (DFT); Halogen; RuAAC; Triazoles